The Glorious Summer - Orrill, Toni (Hamilton Books, 2007)
The Glorious Summer is a personal account of a cross-country journey of soul-searching and rediscovering the Christian faith. Along the way, the author learned to see the world in a new and remarkable way, and to accept circumstances as part of a higher purpose. This work captures a startlingly original voice in search of God, and uncovers divine answers through observations on natural beauty and supernatural love. The reader accompanies Orrill on her ride through the valley of divorce, the loneliness of an empty nest, and the eventual blessing of single-hood, where she arrives at an incredible place of surrender to the will of God. The universal gems of wisdom shared within are sure to be a fresh spiritual drink for contemporary women. The Glorious Summer will be remembered as one of the most honest and illuminating works of modern Christian memoirs. Please visit the author's website at: http://theglorioussummer.com/